2014
DOI: 10.1155/2014/259836
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and Acceleratory Effects of Inonotus obliquus on Tyrosinase Activity and Melanin Formation in B16 Melanoma Cells

Abstract: The aim of the present study is to preliminarily investigate the antimelanogenesis effect of Inonotus obliquus extracts by cell-free mushroom tyrosinase assay. It was found that petroleum ether and n-butanol extracts might contain unknown potential tyrosinase inhibitors, while its ethyl acetate extract might contain some unknown accelerators. Six compounds were isolated and their structures were identified by interpretation of NMR data and nicotinic acid was first discovered in Inonotus obliquus. In cells test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Phenolic compounds have been reported to be responsible for the anti-tyrosinase activity of mushroom extracts, but Yan et al [24] also isolated two steroidal triterpenes (betulin and trametenolic acid) from Inonotus obliquus (Ach. ex Pers.)…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds have been reported to be responsible for the anti-tyrosinase activity of mushroom extracts, but Yan et al [24] also isolated two steroidal triterpenes (betulin and trametenolic acid) from Inonotus obliquus (Ach. ex Pers.)…”
Section: Resultsmentioning
confidence: 99%
“…Among three lanostane triterpenoids, inotodiol alone was reported to inhibit cancer cell proliferation (16). In comparison, inotodiol and lanosterol reportedly increased tyrosinase activities as well as melanin content in B16 melanoma cells (37). Further, it has been shown that the activity of another triterpene lanostane, ganoderic acid, on the growth and invasiveness of cancer cells is linked to the hydroxylation of its structure, as the inactive compound is not hydroxylated (38), suggesting that hydroxylation of lanosterol may be responsible for its potent immunological activities.…”
Section: Discussionmentioning
confidence: 97%
“…Pilát, also known as "chaga mushroom" is a medicinal mushroom commonly used in Russia and other North-European countries with reported anti-tumour and immunomodulatory properties (Taofiq et al, 2016). Studies were conducted by Yan et al (2014) who investigated the tyrosinase inhibitory activity of petroleum ether and n-butanol extracts of Inonotus obliquus. At 10 Mg/mL, petroleum ether and n-butanol extracts showed tyrosinase inhibitory activity with IC 50 value of 3.81 and 6.32 Mg/mL, respectively.…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%